METHODS AND ACTIVITIES OF HEALTH COMPETENCE DEVELOPMENT IN NON-FORMAL ENVIRONMENT: EXPERIENCE OF CHILDREN WITH TYPE 1 DIABETES MELLITUS - Čergelytė-Podgrušienė, Indrė; Gudžinskienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Diabetes mellitus is a disease when certain processes in the body, which maintain a normal blood glucose concentration, get imbalanced. Research object is educational methods and activities used for the development and training of health competence. The aim of the research is to reveal educational methods and activities used for the development of health competence in non-formal environment, based on the experience of children with type 1 diabetes mellitus. Research methods: theoretical – analysis, comparison, and generalization of scientific literature; empirical – the use of focus group discussions with children with diabetes mellitus for data collection; Empirical research revealed that various educational methods and activities aimed at developing health competences are carried out for children with type 1 diabetes mellitus in non-formal educational environments (medical facilities, summer camps and health camps). The following activities and classes are used in medical facilities: lessons, conversations, questionnaires, and games. Activities used in summer camps are as follows: walks, cycling, games designed to develop physical activity skills. In the educational environment of health cams, the following educational methods and activities are used for the development of health competence for children with type 1 diabetes mellitus: lessons, games, educational activities, trips, and creative activities.